ANCA-associated vasculitis and pauci-immune glomerulonephritis in HIV disease. (1st April 2014) - Evans, Rhys; Gueret-Wardle, Alexander; Edwards, Simon; Salama, Alan
Abstract : We report the case of a 51-year-old African woman with longstanding well-controlled HIV who developed relapsing systemic antineutrophil cytoplasm antibody (ANCA)-associated vasculitis and glomerulonephritis. She presented with an acute kidney injury and heavy proteinuria in the setting of a prolonged history of diffuse arthralgias and transient ocular symptoms. Antimyeloperoxidase (MPO) antibody titre was >100 IU/mL. Subsequent renal biopsy demonstrated a focal necrotising pauci-immune glomerulonephritis and a diagnosis of MPO-ANCA-associated microscopic polyangiitis was made. The patient was treated with tapering glucocorticoids and rituximab with resolution of her acute kidney injury and reduction in her proteinuria. Treatment was complicated by the development of steroid-induced diabetes and one mild clinical relapse, but was otherwise well tolerated without infectious complications or deterioration in her HIV disease.